If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(8x+2)=9+2(3x-5)
We simplify the equation to the form, which is simple to understand
3(8x+2)=9+2(3x-5)
Reorder the terms in parentheses
+(+24x+6)=9+2*(3x-5)
Remove unnecessary parentheses
+24x+6=+9+2+*(+3x-5+)
Reorder the terms in parentheses
+24x+6=9+(+6x-10)
Remove unnecessary parentheses
+24x+6=+9+6x-10
We move all terms containing x to the left and all other terms to the right.
+24x-6x=+9-10-6
We simplify left and right side of the equation.
+18x=-7
We divide both sides of the equation by 18 to get x.
x=-0.388888888889
| z^2-(5+2i)*z+21+i=0 | | z^2-(5+2i)*z+2i+i=0 | | x/3+2=10 | | 2x/5=8 | | 4a+3b=63 | | 42=9c/5+32 | | 6*6+-3*-3-8*8= | | 2*6*-3/8= | | 3*6*-3= | | 4x-5-2x=x+1 | | x^2+x-54=0 | | 3x+6=5x-4 | | 4a+3b+c=64 | | x-[11+2x-(4x+7)]=x-8 | | 2+y=-1 | | 3+y=9 | | 7-10x=127-31x | | 7+7x=25-x | | 2x^2-18x=-3x^2-7x-6 | | 5x^2-5x+8=2 | | y=0.67x+4 | | 63=3x+4y | | 2(x+35)=X+130 | | Y=36x+20 | | 4w=-16 | | (10x+3)(2x^2-5x-3)=0 | | 48x^3-16x^2-4x=0 | | t^2+t=12 | | x(2x-3)=27 | | 2*(100-50)= | | 5y-1+3x+6=180 | | 12-7(3t+2)=5t |